STRATEGIC MANAGEMENT OF AN AGRICULTURAL ENTERPRISE UNDER MARTIAL LAW CONDITIONS - Mahiiovych, Ruslana (Social Development: Economic and Legal Issues, 2026)
The article examines the theoretical and practical aspects of strategic management of agricultural enterprises under martial law conditions. It is determined that the agricultural sector of Ukraine operates under significant transformational challenges caused by military actions, destruction of infrastructure, disruption of logistics chains, limited access to financial resources, labor shortages, inflationary processes, and instability in domestic and foreign markets. These factors significantly affect the efficiency and competitiveness of agricultural enterprises and require the implementation of adaptive management approaches. The study identifies the main risks and threats affecting the stable functioning of agricultural enterprises in crisis conditions. Particular attention is paid to logistical difficulties, rising production costs, declining investment attractiveness, energy supply problems, and changes in export opportunities. It is substantiated that effective strategic management during wartime should be based on flexibility, rapid adaptation to changes in the external environment, diversification of production and distribution channels, as well as strengthening the economic resilience of enterprises. The article emphasizes the importance of implementing crisis management mechanisms, digital technologies, innovative management tools, and modern information systems to improve the effectiveness of managerial decision-making. The role of strategic planning, risk management, resource optimization, and financial sustainability in ensuring the continuity of agricultural production is highlighted. The necessity of state support, international cooperation, and investment stimulation for the recovery and development of the agricultural sector is also substantiated. Practical directions for improving the efficiency of agricultural enterprises under current economic conditions are proposed, including diversification of activities, implementation of energy-saving technologies, development of export potential, strengthening food security, and enhancing competitive advantages in domestic and foreign markets. It is concluded that strategic management is a key factor in ensuring the resilience, adaptability, and long-term development of agricultural enterprises under martial law conditions.